Prolonged Inhibition of Acute Arterial Thrombosis by High Dosing of a Monoclonal Anti-platelet Glycoprotein IIb/IIIa Antibody in a Baboon Model - Kotzé, H F; Badenhorst, P N; Lamprecht, S; Meiring, M; Wyk, V Van; Nuyts, K; Stassen, J M; Vermylen, J; Deckmyn, H (Thrombosis and Haemostasis, 1995)
The in vivo activity of MA-16N7C2, the first monoclonal antibody that contains an echistatin-like RGD-sequence and inhibits platelet glycoprotein (GP)IIb/IIIa function, was determined in baboons. A dosefinding study assessing haemostatic variables such as bleeding time and ex vivo platelet aggregation showed that doses of as low as 0.2-0.3 mg/kg resulted in a pronounced effect. The effects were dose-dependent and lasted for several days, implying that MA-16N7C2 is a potent and long-acting GPIIb/IIIa inhibitor. Following the initial studies, the antithrombotic effect of 0.1 and 0.3 mg/kg of the antibody, given as a bolus, was determined in a baboon model of platelet-dependent, arterial-type thrombus formation. In these studies, a thrombogenic device consisting of Dacron vascular graft material was inserted as extension segments into a permanent arteriovenous shunt. The results confirmed the potent and long-lasting antithrombotic effect of MA-16N7C2. Surprisingly, the antithrombotic effect was stronger 48 h after a dose of 0.3 mg/kg administration than on the day of treatment with 0.1 mg/kg, despite the fact that comparable numbers of GPIIb/IIIa receptors were occupied on resting platelets. We postulate that with the high dose of MA-16N7C2 and after an extended period, occupied GPIIb/IIIa may be internalised by the platelets. Upon platelet activation, these receptors become reexposed but arc unable to participate in thrombus formation. This is in contrast to unoccupied internal GPIIb/IIIa receptors early after a low dose of MA-16N7C2.